Lea remains vocal in a time of trolls and fake news (Philippine Daily Inquirer, 2019)
Her mom Ligaya constantly gets anxious whenever singer-actress Lea Salonga fearlessly expresses her views in cyberspace. Visit us at the College of Music Library for more details of the article.